Cosmetics and its Health Risks (Global Journal of Medical Research, 2018)
The use of cosmetic products is increasing around the world and a variety of chemical compounds used in the manufacture of these products grows at the same time. In this way, the risk of intoxication, allergic processes, prolonged chemical exposure, side effects and indiscriminate use are also increased. The present work aims to highlight the biological risks that cosmetics can pose to human health against the toxic substances used in its formulation. This work is an integrative literature review structured according to the methodology described by Whittemore, R. and Knafl, K., 2005. This work relates the main toxic chemical substances present in cosmetic products to the possible health complications reported in the scientific literature. Currently, the cosmetic industries have increased the use of compounds with preservative action, surfactant, fragrances, stains, etc. in the formulation of cosmetic products. Such substances potentiate the quality, property and shelf life of cosmetics, but on the other hand, many of these substances are toxic to the human body, presenting health risks ranging from a simple mild hypersensitivity reaction to an anaphylactic process or even a lethal intoxication. Thus, the indiscriminate use of cosmetics may present itself as an emerging issue of public health. In view of the above, this work seeks to encourage improvements in the search for new methodologies for quality control in the production and consumption of cosmetic products around the world.
Keywords: cosmetics; biological risks; toxicity; quality control; adverse effects